Development of mathematical model for monorail suspension system under different track conditions - Bakhit Mabrouk, Wafi Adam (2015)
Traffic problems in major cities around the world during the last two decades have presented important needs of new transportation systems. Currently, there is an increased demand on public transportation systems, especially in mega cities. This increased transportations demand, pushed transportation authorities to plan new projects and expand existing monorail systems to accommodate the increase demand. This required engineers to develop and design larger monorail systems. New Monorail designs require more powerful bogies with new dimensions to accommodate more passengers, therefore new suspension system design is essential. In order to overcome new designs problems, better understanding of the suspension system is needed by mathematically modeling the system to predict some dynamic characteristics of a new design. This research work concentrates on the modeling and simulation of 15 degrees of freedom full-car Monorail suspension system. The model features the Monorail body, Front bogie and rear bogie geometries. Lagrange’s equation was used to obtain the equations of motion of the monorail suspension system and system matrices. Numerical Central Difference method was used to obtain the system responses subject to sinusoidal Track excitations. Three Track scenarios that has different loads and different driving speeds were conducted to investigate the monorail suspension system, programmed in MATLAB. The system results are analyzed in terms of their dynamic responses. Fourier Fast transform was used to calculate the frequency ranges of dynamic responses. As a result, some very important characteristics of the Monorail suspension system were revealed, with indicators that helps understanding the effects of driving speeds and different loads, which can be used to better understand the system dynamic performance, to improve the original design specifications and detect Monorail suspension system problems.